ECONOMIC AND ENERGY EFFICIENCY OF THE IMPROVED ELEMENTS OF SUNFLOWER CULTIVATION TECHNOLOGY IN THE RIGHT-BANK STEPPE OF UKRAINE - Pinkovsky, G. V.; Tanchyk, S. P. (Scientific Progress & Innovations, 2019)
The article presents the results of scientific research on economic and energy efficiency of the improved elements of sunflower cultivation technology in the Right-Bank Steppe of Ukraine. The research has shown that early sowing time determines a higher level of profitability as compared with later ones. It was also established that production costs during the first sowing period varied between 8,677–9,835 UAH/ha, during the second one – 8,793–9,951 UAH/ha, and during the third one the expenses grew to 8,909–10,067 UAH/ha because of conducting additional pre-sowing tillage during the second term and two during the third one. Taking into account the economic indicators, it is profitable to grow the LG 54.85, LG 55.82 hybrids in the first term of sowing at soil temperature of 5–6 °C. Forward and LG 56.32 sunflower hybrids ensure the highest economic indicators during the third sowing period at soil temperature of 9–10 °C. Among hybrids, it is most economically expedient to grow LG 55.82 when sown at soil temperature of 5–6 °C. The net profit resulting from this option amounted to 22,043 UAH/ha, the level of profitability – 224.1 %. Energy efficiency ratio was the highest in case of the first sowing period for the LG 55.82 hybrid and made up 4.44. Economic and energy efficiency largely depends on the morphological peculiarities of the hybrids, plant density, sowing time, and cultivation technology. It was established that the cultivation of Forward, LG 56.32, LG 54.85, LG 55.82 hybrids is economically and energetically expedient with plant density of 60 thou/ ha. High requirements of sunflower to the environmental resources do not exclude early terms of sowing, but on the contrary, confirm the relevance of the research as to their efficiency.